Design, Synthesis and Preliminary Pharmacological Screening (antimicrobial, analgesic and anti-inflammatory activity) of Some Novel Quinazoline Derivatives - Biswajit Dash, Suvakanta Dash, Damiki Laloo, Chitrani Medhi (Journal of Applied Pharmaceutical Science, 2017)
Objectives: The present research work is designed to synthesize some new series of quinazoline-4-one/4-thione derivatives by modifying the structures retaining the fundamental structural features for the biological activity and screened for their anti-microbial, analgesic and anti-inflammatory properties.Material and methods: A series of 7-chloro-3-[substituted (amino/phenyl amino)]-2-phenyl quinazolin-4(3H)-one/thione derivatives and 1-(7-chloro-4-oxo/-2-phenylquinazoline-3-(4H-yl))-substituted urea derivatives were prepared and characterized from different spectra and elemental analysis. The anti-microbial, analgesic and anti-inflammatory activity were investigated by agar diffusion cup plate method, tail immersion method and carrageenan-induced paw oedema method respectively.Results: The physico-chemical and spectroscopic data confirmed the synthesis of quinazoline derivatives. Five compounds (IIc, IIg, IIh, IIi and IIj) showed good activity against microbes and two compounds (IIc and IIg) showed good activity profile against both pain and inflammation. Three compounds (IIh, IIi and IIj) shows good therapeutic activity only against inflammation.Conclusion: The quinazoline derivatives obtained indicates that the methyl/methoxy group in phenyl hydrazine ring, amine, urea and thiourea substitution at 3rd position of quinzoline ring are essential for anti-microbial, analgesic and anti-inflammatory activity. Compounds IIc, IIg, IIh, IIi and IIj were found to be potent which may be effective as potential source for the development of anti-microbial, analgesic and anti-inflammatory compound.
Keywords: 7-chloro-2-phenyl-4H-benzo[d][1,3]oxazin-4-one, quinazoline derivatives, anti-microbial activity, analgesic and anti-inflammatory activity.